Internalization of Rahmatan lil 'Alamin Values for Student Tolerance: Internalisasi Nilai-Nilai Rahmatan lil 'Alamin untuk Toleransi Siswa - Syamsadea, Alya Rafika; Amrullah, Muhlasin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Education in elementary schools plays a crucial role in shaping students’ character and tolerance in a diverse society. Specific Background: Despite efforts to promote harmony, many students still lack respect for peers, often disturbing others and showing intolerance. Knowledge Gap: Previous studies have emphasized the cognitive understanding of Islamic values but less attention has been given to their consistent internalization in daily school practices. Aims: This study explores the internalization of Rahmatan lil ’Alamin values in religious activities to foster tolerance, justice, and social responsibility among elementary students. Results: Findings show that embedding moderation, non-violence, compassion, and respect for diversity through religious practices and teacher collaboration contributes to students’ tolerance, intercultural sensitivity, and harmonious interactions. Novelty: The study highlights a practical model of value internalization through structured activities, integrating moral and spiritual aspects of Islam into daily learning. Implications: The approach offers educators a pathway to reduce intolerance and extremism while nurturing inclusive, socially responsible, and peaceful young generations Highlights: Internalization of Rahmatan lil ’Alamin values strengthens tolerance in students. Teacher collaboration is central in shaping inclusive school practices. Religious activities become effective platforms for moral and social education. Keywords: Internalization, Rahmatan lil ’Alamin, Tolerance, Elementary Education, Character